Exon skipping and inclusion therapies methods and protocols - Yokota, Toshifumi ca. 20./21. Jh; Maruyama, Rika ca. 20./21. Jh (Methods in Molecular Biology, 2018)
This book presents a comprehensive collection of detailed state-of-the-art exon skipping and splices modulation protocols. Chapters detail 14 genetic diseases, AON-mediated therapies, and CRISPR/Cas9-mediated gene editing therapies. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Exon Skipping and Inclusion Therapies: Methods and Protocols aims to help researchers initiate the development of next-generation therapies